Photoluminescence and mechanoluminescence of solid‐state zirconocene dichlorides. (8th February 2021) - Tukhbatullin, Adis A.; Kovyazin, Pavel V.; Sharipov, Glyus L.; Parfenova, Lyudmila V.; Ivchenko, Pavel V.; Nifant'ev, Ilya E.
Abstract: Spectral‐luminescence properties of 23 samples of zirconium complexes were studied. Mechanoluminescence spectra of 10 complexes were obtained. The solid‐state component of the mechanoluminescence spectrum, that is the luminescence of the crystal itself, coincided with the photoluminescence spectra of these complexes, which indicated identical emission from the same excited states in mechanoluminescence and photoluminescence, despite the different ways of excitation. The luminescence maximum was red shifted as substituents appeared in the ligand, in particular in the presence of a bridging group connecting π‐ligands (ansa‐complexes) and also for a substituted bis‐indenyl complex rac‐ Me2 Si(2‐Me‐4‐Ph‐5‐OMe‐6‐Bu t ‐Ind)2 ZrCl2 ). It was found that mechanical destruction of the rac‐ isomer of complex Mе2 С(2‐Me‐4‐Bu t ‐C5 H2 )2 ZrCl2, unlike that of the meso‐ isomer, was accompanied by a more than a 10‐fold increase in intensity and by a shift in the mechanoluminescence spectrum to longer wavelengths. Abstract : The study showed that varying the ligand structure is an important tool for controlling the luminescence properties of metal complexes. Further design and synthesis of zirconocenes would be attractive, both for the development of new photosensitizers based on cheaper and more accessible Ti subgroup metals and for using these complexes as luminescent probes for studying mechanisms of heterogeneous catalysis.